The effects of human needs as stipulated in Maqasid Syariah on zakah distribution effectiveness / Maheran Zakaria, Wan Murshida Wan Hashim and Nazmi Mohd Zain - Zakaria, Maheran; Wan Hashim, Wan Murshida; Mohd Zain, Nazmi (Research Management Institute (RMI), 2013)
The objective of this study is to investigate the influence of human needs in the perspective of Maqasid Syariah namely religion, physical-self, knowledge, family and wealth on zakat distribution effectiveness. Approximately 350 sets of questionnaire were personally sent to zakat recipients of two programs conducted by Majlis Agama Islam Kelantan (MAIK) namely business assistance and living skill course. From this amount, 320 people responded, amounting to 91.43 % response rate. Data were analyzed using Social Science Statistical Package (SSPS) 20 and Analysis of Moment Structurzakahe (AMOSS) 20. From the findings, it can be concluded that all human needs in the perspective of Maqasid Syariah namely religion, knowledge, physicalself, family and wealth positively influence zakah distribution effectiveness. Hence, the study provides an insight to zakat institutions, policy makers and the public that the effectiveness of zakah distribution could not only be judged in terms of monetary value but also to other non-monetary values that include religion, physical life, knowledge, family and wealth.